Cell-free layer measurements in a network with bifurcating microchannels using a global approach - Bento, David (2018)
One of the most interesting hemodynamic phenomenon observed in microchannels is the existence of a marginal cell-free layer (CFL) at regions adjacent to the wall. This is a well known phenomenon that occurs in simple glass capillaries and in vivo microvessels, but has never been investigated in detail in biomedical microdevices containing complex geometries. In the present chapter, in vitro blood flowing through bifurcating microchannels was studied, with the aim of characterizing the cell-free layer (CFL). For that three different videos with different hematocrit and flow rates were considered. All images were obtained by means of a high-speed video microscopy system and then processed in MatLab using the Image Processing toolbox. The numerical data was obtained automatically and analyzed by optimization techniques using the genetic algorithm approach. The results suggest that the CFL were formed in a similar way at the upper and lower regions in all bifurcations.